2009
DOI: 10.1097/mat.0b013e3181bea710
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Profiling, But Not Cool Dialysate, Increases the Absolute Plasma Refill Rate During Hemodialysis

Abstract: Intradialytic hypotension is often caused by a discrepancy between ultrafiltration and plasma refilling. Increasing the plasma refill rate could therefore reduce intradialytic hypotension. We used a recently developed method to measure the effect of cool dialysate and sodium (Na) profiling on refill during hemodialysis (HD). Using a Gambro AK200 with blood volume (BV) sensor plus computer-guided external pump, a high ultrafiltration rate quickly induced a preset BV reduction. A software feedback mechanism subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Compared with non‐modelled dialysis protocols, sodium modelling has been associated with higher mean arterial pressures and higher post‐HD blood pressure . The beneficial effects of sodium modelling are thought to be mediated by blunted fluid shifts between the intravascular and intracellular spaces …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with non‐modelled dialysis protocols, sodium modelling has been associated with higher mean arterial pressures and higher post‐HD blood pressure . The beneficial effects of sodium modelling are thought to be mediated by blunted fluid shifts between the intravascular and intracellular spaces …”
Section: Introductionmentioning
confidence: 99%
“…9,18 The beneficial effects of sodium modelling are thought to be mediated by blunted fluid shifts between the intravascular and intracellular spaces. 12,19,20 Evidence on sodium modelling's effectiveness in outpatient chronic HD patients cannot be generalized to sicker, less stable patients in the ICU with AKI. However, if haemodynamic benefits were confirmed in this population, sodium modelling may be particularly beneficial because the effects of supraphysiological dialysate sodium may be largely mitigated among ICU patients who typically have little oral intake.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium profiling is a modified method of sodium gradient dialysis during which DNa follows a time‐dependent profile. It can increase the extracellular volume and prevent intradialytic discomforts, such as hypotension, muscle cramps, and disequilibrium syndrome; some studies have found an increase in IDWG and thirst during the sodium‐profiled dialysis therapy . In a randomized cross‐over study, the DNa was changed from 155 ‐ 160 mmol/L in the beginning to 140 mmol/L in the last hour of dialysis during the intervention period.…”
Section: Sodium Profilingmentioning
confidence: 99%
“…The most frequent complication caused by ultrafiltration is an excessive reduction in arterial pressure eventually leading to syncope. Intradialytic hypotension is most likely due to excessive reduction in intravascular volume by ultrafiltration, limited vascular refilling from tissues into the vascular space [1], insufficient reduction in venous unstressed volume, poor diastolic filling under reduced atrial pressures, altered cardiac contractility, and impaired vascular reactivity [2]. Intradialytic hypotension has been shown to be an independent predictor of cardiovascular mortality [3].…”
Section: Introductionmentioning
confidence: 99%